Association between oxytocin and receptor genetic polymorphisms and aggression in a northern Chinese Han population with alcohol dependence. (1st January 2017) - Yang, Ling; Wang, Fan; Wang, Meiling; Han, Mei; Hu, Lufeng; Zheng, Minghua; Ma, Ji; Kang, Yimin; Wang, Pengxiang; Sun, Hongqiang; Zuo, Wei; Xie, Longteng; et al.
Highlights: Rs6133010 in the OXTR gene was associated with AD related aggression in northern Chinese Han population. The genotype GG of rs6133010 carriers in AD group had significant anger aggression. The 3-loci interaction combination of rs6133010AG, rs2254298AG and rs53576AA increases risk for AD. Abstract: Objective: Alcohol dependence (AD) is a common chronic brain disorder precipitated by complex interactions between biological, genetic, and environmental risk factors. Aggression often occurs in the context of AD. Previous studies have shown that Oxytocin (OXT) and OXT receptor (OXTR) are involved in the regulation of aggression. The present study investigated whether variations and interactions of OXT and OXTR genes were associated with AD-related aggression in a genetically homogeneous northern Chinese Han population. Methods: Three hundred and twenty-four male AD patients and 510 male healthy controls (HCs) were recruited. A Chinese version of the Buss-Perry Aggression Questionnaire was used as a subjective measurement of aggressive behavior. Three variations, rs2254298, rs53576, and rs6133010 were genotyped using TaqMan and ligase detection reaction for all subjects. Generalized Multifactor Dimensionality Reduction was used to detect interactions between genetic attributes and environmental attributes. Results: The frequencies of alleles and genotypes of rs6133010 were significantly different between AD patients and HCs ( p   <  0.001). In HCs, the effect of genotype GG of rs53576 on hostility aggression was significantly stronger than that of genotype AA and AG ( p  = 0.001 and p  = 0.004, respectively), and the subjects with the interaction combination of rs6133010AA × rs2254298GG × rs53576AG exhibited significant effect on physical aggression ( p  = 0.0107). Conclusion: The present study found that rs6133010 in the OXT gene is associated with AD in the northern Chinese Han population. The polymorphisms of OXT/R may play a key role in the susceptibility of AD-related aggression.